Efektivitas Projek Penguatan Profil Pelajar Pancasila Dalam Pembentukan Karakter Mandiri di Sekolah Dasar - Fernandez, Yulius Jimmi; Sutopo, Yeri; Yuwono, Agus; Avrilianda, Decky; Subali, Bambang (Cetta: Jurnal Ilmu Pendidikan, 2025)
Some students continue to demonstrate a lack of independence in the school environment, evidenced by their failure to bring necessary materials like books and stationery, or by neglecting to complete assignments. Reports indicate that parents are still awaiting directives regarding assignments and the organization of study schedules, presenting teachers with the challenge of fostering student independence. This study seeks to elucidate the effectiveness of the Pancasila student profile strengthening project at SD Negeri 02 Anjongan, Mempawah district, in cultivating a self-sufficient character. This research method employs a qualitative framework with a descriptive approach. Data were collected through interviews conducted with principals, teachers, and parents. Observations were conducted on fifth-grade students, with documentation to record events associated with the execution of activities. Data is obtained through the collection of information via interviews, observations, and documentation. The acquired data will subsequently undergo processing through reduction, presentation, and the formulation of conclusions. The research indicates that the development of self-sufficient characteristics in students can be achieved through the initiative of enhancing the Pancasila student profile, supported by a positive school culture and collaborative engagement among principals, teachers, parents, and students. In conclusion, the initiative to enhance the Pancasila learner profile demonstrates its effectiveness in fostering independent character development among elementary school students, supported by their interests in talent, environmental stewardship, creativity, collaboration, and a focus on student-centered learning.